(untitled) (Tempo e Argumento, 2021)
Listening to undergraduate students in the 4 supervised internships available at the Department of History of the Federal University of Ouro Preto (UFOP), I have noticed that 2 themes frequently appear and reappear: a) a certain lack of interest, at least initially, of basic education students in the past, in history, and in History teaching, especially with regard to a specific way of relating to the past times: the epistemological-critical-pragmatic; and also b) a certain questioning by the students (sometimes even more energetic/violent) of certain interpretations proposed by teachers. We have been thinking about these challenges throughout our courses, so this article addresses part of our discussions on the themes of temporality and post-truth, especially concerning a certain lack of interest in history and the History teaching. And, finally, we thematize an epistemological behavior through which a certain re-enchantment of history and History teaching could be possible, what I call poetic truth. Keywords: temporality; post-truth; poetic truth.